Gender Policies and Armed Forces in Latin America's Southern Cone - Frederic, Sabina (2015)
In Latin America's Southern Cone, particularly in Argentina, the socio-professional integration of women into the Armed Forces was narrowly geared to a specific scenario : human rights enlargement. Its general inspiration derives from post-dictatorial processes experienced throughout the region. The purpose of this article is to compare the integration of military women in Argentina, Brazil, and Chile. It analyzes the main legislative and regulatory modifications adopted in that regard during the last decade and a half. Its authors show that gender policies within the armed forces were developed in pace with the democratization in each national State. This resulted in significant disparities between the three countries. Such dissimilarities have not been countered by regional and international organizations such as UNASUR (Union of South American Nations, notably through its parent South American Defense Council) and the United Nations (though UN Resolution 1325 certainly played a stimulating role, and its respective influence on each country gives rise to a specific discussion). The study ends with a section providing basic statistical information on the relative increase in the number and share of servicewomen, their distribution by service, corps, and specialties, as well as the standards on which those policies were based in each nation.